Enteric Infections in Young Children are Associated with Environmental Enteropathy and Impaired Growth. Issue 1 (11th December 2017) - George, Christine Marie; Burrowes, Vanessa; Perin, Jamie; Oldja, Lauren; Biswas, Shwapon; Sack, David; Ahmed, Shahnawaz; Haque, Rashidul; Bhuiyan, Nurul Amin; Parvin, Tahmina; Bhuyian, Sazzadul Islam; Akter, Mahmuda; et al.
Abstract: Objective: To investigate the relationship between faecal contamination in child play spaces, enteric infections, environmental enteropathy (EE) and impaired growth among young children. Methods: A prospective cohort study was conducted of 203 children 6–30 months of age in rural Bangladesh. Stool samples were analysed by quantitative PCR for Shigella, Enterotoxigenic Escherichia coli (ETEC), Campylobacter jejuni, Giardia intestinalis and Cryptosporidium spp. Four faecal markers of intestinal inflammation were also measured: alpha‐1‐antitrypsin, myeloperoxidase, neopterin and calprotectin. Child growth was measured at baseline and 9 months after enrolment. E. coli was measured in soil in child play spaces. Results: Forty‐seven percent of study children had three or more enteric pathogens in their stool. Thirty five percent (71/203) of children had Shigella, 30% (61/203) had ETEC, 73% (148/203) had C. jejuni, 79% (160/203) had Giardia intestinalis and none had Cryptosporidium . Children with ETEC had significantly higher calprotectin concentrations (Coefficient: 1.35, 95% Confidence Interval [CI]: 1.005, 1.82). Children with Shigella had a significantly higher odds of being stunted at our 9‐month follow‐up (OR: 2.01, 95% CI: 1.02, 3.93). Children with Giardia intestinalis had significantly higher E.coli counts in the soil collected from their play spaces (OR: 1.23, 95% CI: 1.02, 1.48). Conclusion: Enteric infections were significantly associated with EE and impaired growth in rural Bangladesh. These findings provide further evidence to support the hypothesis that contaminated soil in child play spaces can lead to enteric infections, many of which are likely subclinical, resulting in EE and impaired growth in young children.